What does a teacher need to know in order to teach history? How do students in their initial training interpret this question? - Cavalcanti, Erinaldo Vicente (2025)
The article aims to broaden the reflections about the teaching knowledge in the initial training of the history teacher. To do so, it analyze how a group of 115 students enrolled in the undergraduate course of the Federal University Pará (UFPA) interpret the question what is necessary to teach history. As methodology, a questionnaire was applied, adopting in sequence the quanti-qualitative procedures by which the data were catalogued and tables and graphs about gender, age, color and period in which the participating students were enrolled were produced. Next, the records of the answers produced are analyzed, questioning the knowledge that future teachers understand as necessary for teaching. The data produced shows a great diversity of knowledge profiling the interpretations of the students involving the knowledge of the area of reference, of neighboring areas and of their own experience.